β-blockade with nebivolol for prevention of acute ischaemic events in elderly patients with heart failure - G. Ambrosio; M. D. Flather; M. Böhm; A. J.S. Coats; L. Tavazzi; D. J. van Veldhuisen; M. G. Conti; G. Spinucci; F. Mascagni; A. Murrone; A. Cohen-Solal (Кардиоваскулярная терапия и профилактика)
Aim. This subanalysis of the Study of the Effects of Nebivolol Intervention on Outcomes and Hospitalisation in Seniors with Heart Failure (SENIORS) investigates whether treatment with nebivolol, a β-blocker with nitric oxide-releasing properties, can provide additional benefits besides its effects on heart failure (HF), by reducing cardiac ischaemic events in patients with HF of ischaemic aetiology. Material and methods. A double-blind, randomised, placebo-controlled, multicentre trial of nebivolol in 2128 elderly patients. For this analysis, data were extracted for 2128 elderly (≥70 years) HF patients in whom coronary artery disease (CAD) was the underlying aetiology (68,2 %; 717 placebo-treated patients and 735 assigned to nebivolol). The main endpoint was the composite of cardiac ischaemic events at 2 year follow-up: death/hospitalisation for myocardial infarction, unstable angina or sudden death, as originally identified in the case report form. Results. At follow-up, nebivolol treatment was associated with a one-third reduction in the risk of ischaemic events, the composite endpoint occurring in 15,9 % of placebo and 10,7 % of nebivolol-treated patients (HR 0,68; 95 % CI 0,51 to 0,90; p=0,008). This effect was independent of age, gender and ejection fraction. No difference in this composite endpoint was observed in the subgroup of patients of non-ischaemic aetiology. Conclusion. Nebivolol was effective in reducing cardiac ischaemic events in patients with HF of ischaemic aetiology. The prevention of ischaemic events can be an additional beneficial effect of β-blockade in HF patients with underlying CAD.